2019
DOI: 10.3389/fpsyg.2019.00834
|View full text |Cite
|
Sign up to set email alerts
|

Work-Family Segmentation Preferences and Work-Family Conflict: Mediating Effect of Work-Related ICT Use at Home and the Multilevel Moderating Effect of Group Segmentation Norms

Abstract: Drawing on boundary theory, we propose a multilevel model that examines the effects of group segmentation norms on individual-level processes, relating segmentation preferences to work-family conflict via the use of a technological boundary. Data from 350 married employees in 81 working groups were used to test the model. The results of multilevel analysis revealed that work-related information and communication technology (ICT) use at home mediated the relationship between employee work-family segmentation pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 56 publications
(93 reference statements)
0
23
0
Order By: Relevance
“…Park et al (2011) showed that high organizational norms for segmentation ensured that employees segmented their use of technology. Yang et al (2019) showed that group norms moderated the relationship between segmentation preferences and work‐related technology use at home. In another study, integrators who had low perceptions of organizational integration norms were able to use work‐related PC/laptops at home without feeling time‐based or strain‐based WFC (Gadeyne, Verbruggen, Delanoeije, & De Cooman, 2018).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Park et al (2011) showed that high organizational norms for segmentation ensured that employees segmented their use of technology. Yang et al (2019) showed that group norms moderated the relationship between segmentation preferences and work‐related technology use at home. In another study, integrators who had low perceptions of organizational integration norms were able to use work‐related PC/laptops at home without feeling time‐based or strain‐based WFC (Gadeyne, Verbruggen, Delanoeije, & De Cooman, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…To achieve their preferences, people with high segmentation preference employ boundary work tactics to separate life domains (Kreiner et al, 2009). For example, they avoid work-related technology at home, which in turn improves psychological detachment and reduces WFC (Park, Fritz, & Jex, 2011;Yang, Zhang, Shen, Liu, & Zhang, 2019). Other studies confirmed that high segmentation preference is associated with psychological detachment (Hahn & Dormann, 2013) and also with less emotional exhaustion (Foucreault, Ollier-Malaterre, & M enard, 2018).…”
Section: Segmentation Preference As a Moderatormentioning
confidence: 99%
“…Boundary theory remains the dominant framework used by scholars to explain and deepen the understanding of how individuals build and manage work life and family life boundaries to achieve work-life balance (Allen et al, 2015;Yang et al, 2019). The boundary theory as propounded by Ashforth et al (2000) suggests that work duties and family roles boundaries are interwoven, with significant effects on individuals' time and efforts.…”
Section: Boundary Theorymentioning
confidence: 99%
“…The boundary theory as propounded by Ashforth et al (2000) suggests that work duties and family roles boundaries are interwoven, with significant effects on individuals' time and efforts. Individuals create diverse role boundaries in reflection of the nature of their work functions and family responsibilities to prevent or minimize conflicts from the interface (Yang et al, 2019;Allen et al, 2015).…”
Section: Boundary Theorymentioning
confidence: 99%
See 1 more Smart Citation